2022
DOI: 10.1029/2021gc010127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Matrix Rheology on Stress Concentration in Embedded Brittle Clasts

Abstract: Frictional failure is the dominant deformation mechanism for rocks in the upper crust while in the middle crust rocks begin to deform viscously. Within this transition, brittle and viscous phases coexist, forming semi‐frictional materials. While semi‐frictional deformation on large scales might play an important role in understanding the transition between earthquakes and slow slip/creep, it can also be observed at smaller scales. Here, we use field observations of the Papoose Flat pluton in eastern California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…For moderate clast fractions (>0.3), "jamming" of clasts creates load-bearing force chains that amplify clast stresses by 2-14×, depending on clast-matrix strength contrast (Beall et al, 2019a(Beall et al, , 2019bCates et al, 1998;Webber et al, 2018). Even at low clast fractions (<0.1) and in the absence of clast-clast interaction, clast stress shadows, and the matrix itself, can impose stress on clasts resulting in stress amplification of 2-5× that on the matrix (Ioannidi et al, 2022;Ladd & Reber, 2020). These numerical models, experiments and geologic studies are scale independent, and are consistent with the microstructures observed here reflecting stress amplification in strong actinolite due to force-chain formation and/or stress transfer from the weak talc matrix.…”
Section: Strain Rate Variations and Slow Slipmentioning
confidence: 99%
“…For moderate clast fractions (>0.3), "jamming" of clasts creates load-bearing force chains that amplify clast stresses by 2-14×, depending on clast-matrix strength contrast (Beall et al, 2019a(Beall et al, , 2019bCates et al, 1998;Webber et al, 2018). Even at low clast fractions (<0.1) and in the absence of clast-clast interaction, clast stress shadows, and the matrix itself, can impose stress on clasts resulting in stress amplification of 2-5× that on the matrix (Ioannidi et al, 2022;Ladd & Reber, 2020). These numerical models, experiments and geologic studies are scale independent, and are consistent with the microstructures observed here reflecting stress amplification in strong actinolite due to force-chain formation and/or stress transfer from the weak talc matrix.…”
Section: Strain Rate Variations and Slow Slipmentioning
confidence: 99%
“…Most garnet porphyroclasts studied previously were metamorphosed under eclogite facies conditions (Yamato et al, 2019;Rogowitz et al, 2023) and hence are embedded in an omphacite-bearing matrix, the rheology of which is much stronger than quartz as for our experiment. A stronger matrix would enable the accumulation of stresses sufficient to produce deformation within the clast under a lower strain rate rather than in the weak matrix (e.g., Beall et al, 2019a;Ioannidi et al, 2022). Yamato et al (2019) found that locally increased stresses at the grain boundaries of garnet crystals can reach their yield strength and cause frictional failure; this deformation might be analogous to our Style 2 deformation.…”
Section: Comparison With Previous Studiesmentioning
confidence: 85%
“…Since in our models we use regular quadratic mesh, elements on the borders of circular garnets contain markers of both materials (inset of Figure 3a). Existence of both types of markers in one element results in the averaging of rheological properties of that element and leads to localization of stresses and subsequently frictional deformation (e.g., Ioannidi et al, 2022).…”
Section: Styles Of Deformationmentioning
confidence: 99%
“…For moderate clast fractions (>0.3), "jamming" of clasts creates load-bearing force chains that amplify clast stresses by 2-14x, depending on clast-matrix strength contrast (Beall et al, 2019a;2019b;Cates et al, 1998;Webber et al, 2018). Even at low clast fractions (<0.1) and in the absence of clast-clast interaction, clast stress shadows, and the matrix itself, can impose stress on clasts resulting in stress amplification of 2-5x that on the matrix (Ioannidi et al, 2022;Ladd & Reber, 2020). These numerical models, experiments and geologic studies are scale independent, and are consistent with the microstructures observed here reflecting stress amplification in strong actinolite due to force-chain formation and/or stress transfer from the weak talc matrix.…”
Section: Strain Rate Variations and Slow Slipmentioning
confidence: 99%